2018
DOI: 10.1002/epi4.12221
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking L‐12/15‐lipoxygenase show increased mortality during kindling despite demonstrating resistance to epileptogenesis

Abstract: SummaryObjectiveStudies have addressed the potential involvement of L‐12/15‐lipoxygenases (LOs), a polyunsaturated fatty acid metabolizing enzyme, in experimental models of acute stroke and chronic neurodegeneration; however, none to our knowledge has explored its role in epilepsy development. Thus, this study characterizes the cell‐specific expression of L‐12/15 ‐LO in the brain and examines its contribution to epileptogenesis.MethodsL‐12/15‐LO messenger RNA (mRNA) and protein expression and activity were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The lack of response to DHA supplementation may be due to the different metabolism of EPA and DHA in the brain and the preferential incorporation of DHA into cell membrane phospholipids, with DHA accounting for up to 40% of all fatty acids in some regions of the brain [33], and EPA mostly subjected to beta-oxidation [34]. However, both EPA and DHA may undergo conversion to SPM in the brain as 15-LOX is expressed by neurons and microglia [35]. In a mouse model of depression, intracranial administration of RvE1-3 or RvD1-2 was associated with reduced symptoms [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of response to DHA supplementation may be due to the different metabolism of EPA and DHA in the brain and the preferential incorporation of DHA into cell membrane phospholipids, with DHA accounting for up to 40% of all fatty acids in some regions of the brain [33], and EPA mostly subjected to beta-oxidation [34]. However, both EPA and DHA may undergo conversion to SPM in the brain as 15-LOX is expressed by neurons and microglia [35]. In a mouse model of depression, intracranial administration of RvE1-3 or RvD1-2 was associated with reduced symptoms [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated its involvement in the pathogenesis of human diseases (Singh and Rao, 2019). In addition, mice lacking leukocyte-type 12/15-LOX were resistant to PTZ-induced epilepsy, which implied that 12/15-LOX might be involved in the process of epileptic seizures (Kanzler et al, 2018). In our study, the expression of 12/15-LOX was increased in the FAC- and erastin-treated HT22 cells and FeCl 3 -induced mice PTE model.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were stored at −20 • C overnight. Total RNA was isolated and first-strand complementary DNA (cDNA) synthesized as described (Kanzler et al, 2018). cDNA samples were amplified for 40 cycles (95 • C for 15sec, 60 • C for 60sec, 95 • C for 15 sec, 60 • C for 15 sec and 95 • C for 50 sec) using Taq DNA polymerase (Invitrogen) and target specific mouse primers for c-fos (Mm00487425_m1, TaqMan Gene Expression Assays, Applied Biosystems, Foster City, CA) and hypoxanthine guanine phosphoribosyl transferase (HPRT, Mm01545399_m1, TaqMan Gene Expression Assays, Applied Biosystems).…”
Section: Behavioral Testsmentioning
confidence: 99%